2009
DOI: 10.1271/bbb.90462
|View full text |Cite
|
Sign up to set email alerts
|

Short-Step Synthesis of a Resveratrol Derivative from Commercially Available 1,3-Dimethoxybenzene and 4-Vinylanisole

Abstract: An efficient synthesis of tri-O-methylated resveratrol is presented using an advanced Heck reaction promoted by Pd(dba) 2 in the presence of P(t-Bu) 3 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Therefore, Pd‐catalyzed cross‐coupling reactions are very effective alternatives due to their synthetic versatility and efficiency 17. Suzuki reactions between β‐halostyrenes and arylboronic acids,18–20 decarbonylative Heck reactions between resorcylic acid chlorides and styrenes,21, 22 and Heck reactions between aryl halides and styrene derivatives regioselectively furnish the trans ‐stilbene coupling products in one step;23–32 however, in all of these cases, a styrene derivative substrate is required. Although some styrene derivatives are commercially available, most need to be prepared by elimination reactions, partial alkyne reductions, carbonyl olefination methods or, more recently, via Pd‐catalyzed cross‐coupling reactions 33.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, Pd‐catalyzed cross‐coupling reactions are very effective alternatives due to their synthetic versatility and efficiency 17. Suzuki reactions between β‐halostyrenes and arylboronic acids,18–20 decarbonylative Heck reactions between resorcylic acid chlorides and styrenes,21, 22 and Heck reactions between aryl halides and styrene derivatives regioselectively furnish the trans ‐stilbene coupling products in one step;23–32 however, in all of these cases, a styrene derivative substrate is required. Although some styrene derivatives are commercially available, most need to be prepared by elimination reactions, partial alkyne reductions, carbonyl olefination methods or, more recently, via Pd‐catalyzed cross‐coupling reactions 33.…”
Section: Introductionmentioning
confidence: 99%
“…was effective ligand to form stilbene framework. 12 Fu reported that the effect of P(t-Bu)3. 13 According to his report, the effect of P(t-Bu)3 is electron donating as well as accelerating reductive elimination.…”
mentioning
confidence: 99%